2015
DOI: 10.1016/j.amjmed.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day Hospital Readmissions in Patients with Non-ST-segment Elevation Acute Myocardial Infarction

Abstract: Background Limited data exist about relatively recent trends in the magnitude and characteristics of patients who are rehospitalized shortly after admission for a non ST-segment elevation acute myocardial infarction (NSTEMI). This observational study describes decade-long trends (1999-2009) in the magnitude and characteristics of patients readmitted to the hospital within 30 days of hospitalization for an incident (initial) episode of NSTEMI. Methods We reviewed the medical records of 2,249 residents of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
(38 reference statements)
4
22
0
Order By: Relevance
“…This is consistent with a small study based in Massachusetts, which looked at seasonality and readmission after MI and found a higher gross readmission rate in winter and spring, but this did not reach statistical significance given small sample size (Tisminetzky et al. ). In context of pneumonia, many diverse studies have found increases in incidence of respiratory bacterial and viral infections and hospitalization for community‐acquired pneumonia in winter or seasons of low temperature (Kim et al.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is consistent with a small study based in Massachusetts, which looked at seasonality and readmission after MI and found a higher gross readmission rate in winter and spring, but this did not reach statistical significance given small sample size (Tisminetzky et al. ). In context of pneumonia, many diverse studies have found increases in incidence of respiratory bacterial and viral infections and hospitalization for community‐acquired pneumonia in winter or seasons of low temperature (Kim et al.…”
Section: Discussionsupporting
confidence: 84%
“…; Tisminetzky et al. ). However, all of these studies have been single‐center reports with small sample sizes and limited adjustment for other characteristics.…”
mentioning
confidence: 98%
“…The current study examines the incidence and predictors of 30‐day readmissions after NSTE‐ACS using a large‐scale administrative database. Despite the relevant burden this problem can pose, few studies have previously analyzed the readmissions rates after NSTE‐ACS . Dunlay et al showed that 18.6% of patients with acute myocardial infarction had a 30‐day readmission between 1987 and 2010 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tisminetzky et al demonstrated a high but stable rate of readmission with NSTE‐ACS over the years 1999–2009. They also found a prolonged index hospitalization and significant baseline comorbidities as significant factors for readmission . Both studies showed a high rate of readmissions with NSTE‐ACS, however, they were derived from a single community database with large number of patients treated in prior decades, time before enormous advances and paradigm shift in the treatment of ACS occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation